Monitoring Sea Level Rise in Malaysia Using Geospatial Technology - Lee, Jia Rong (Universiti Teknologi PETRONAS, 2018)
Climate change has become a worldwide issue. Climate change exists due to development of human and technology which break the natural ecosystem of the Earth. One of the most crucial impacts of climate change is sea level rise, caused by melting of ice glaciers and thermal expansion of sea water. Generally, global mean sea level is being monitored rather than localized mean sea level especially Malaysia. Therefore, there is a necessity to carry out localized sea level monitoring and investigate adaptation capacity in Malaysia. Penang was chosen as study area for this project. Penang, is one of the major coastal cities in Malaysia with high contribution to Malaysia economy and brimming with heritage reserve. Thus, this project monitored sea level using geospatial technology and investigate adaptation capacity in Penang. It was observed that sea level is fluctuating with potential to exceed the highest level (year 2006). Besides, a drastic drop and rise was observed at every five (5) years interval and another drastic fall and rise in sea level is expected to occur in 2018 and 2019 respectively. In comparison to leading Asian cities (Singapore and Seoul, Republic of Korea), Penang’s adaptation readiness is moderate. Therefore, government should introduce policies to strengthen adaptation capacity.